Сто лет пути: [романы] / Татьяна Устинова - Устинова Татьяна Витальевна (Русский бестселлер, 2015)
Экземпляры: ф.6 (20171227) / Инвентарный номер: 2117 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: У 80 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44